Coincidence method for study of secondary particle emission. (August 2021) - Yurasova, V.E.
Abstract: A unique experimental set-up for coincidence measurements is used for the detection of simultaneous emission of two particles, such as an ion and a photon, emitted by this ion immediately after its ejection from the solid. This set-up was also used to measure spatial and energy distributions of secondary excited ions. Quasi-resonant electron exchange between secondary ions and the surface was observed, and a correlation between the surface electronic structure and the yield of secondary ions with a particular energy was discovered. Some of the measured energy spectra of excited secondary ions showed oscillatory behaviour. The obtained results open up the prospect for the use of the coincidence technique to investigate electronic properties of surfaces. The aim of this review is to describe the results of our pioneering use of the coincidence method to study secondary ion, ion-electron and ion-photon emission. Highlights: The creation of a unique experimental set-up for coincidence measurements was done. The single scattering of ions accompanied by ion-electron emission was studied. Correlation of surface electronic structure and secondary ion yield was discovered. Oscillatory energy spectra of excited secondary ions were observed. Electronic properties of surfaces may be studied using obtained results.